“A Most Detestable Crime”: Gender Identities and Sexual Violence in the District of Montreal, 1803-1843 - Ramos, Sandy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
AbstractThis paper explores the ambivalent attitudes of the criminal justice system, and indeed of society as a whole, towards crimes of sexual violence in Montreal from 1803-43. Nineteenth-century society acknowledged that rape was a heinous crime deserving of harsh punishment, yet the courts were confronted with a much murkier reality in which drastically different and gendered accounts of the alleged crime were presented by the accuser, the accused, and the witnesses. Female complainants defined rape in terms of personal violation; the accused conceived of it in the context of negotiation of their sexual access to women; judges and juries conceptualized rape in terms of dominant ideas about appropriate gender relations; and medical doctors understood rape in terms of bodily marks and physical signs. The criminal court for the District of Montreal becomes a microcosm in which societal ideas about relationships between men and women were articulated, constructed, resisted, and imposed.